Race and Insurance Status Association With Receiving Orthopedic Surgeon-Prescribed Foot Orthoses. (July 2021) - Stevens, Trenton T.; Hartline, Jacob T.; Ojo, Oluwatosin; Grear, Benjamin J.; Richardson, David R.; Murphy, G. Andrew; Bettin, Clayton C.
Background: This study looked at the effect of patient demographics, insurance status, education, and patient opinion on whether various orthotic footwear prescribed for a variety of diagnoses were received by the patient. The study also assessed the effect of the orthoses on relief of symptoms. Methods: Chart review documented patient demographics, diagnoses, and medical comorbidities. Eligible patients completed a survey either while in the clinic or by phone after their clinic visit. Results: Of the 382 patients prescribed orthoses, 235 (61.5%) received their orthoses; 186 (48.7%) filled out the survey. Race and whether or not the patient received the orthosis were found to be significant predictors of survey completion. Race, type of insurance, and amount of orthotic cost covered by insurance were significant predictors of whether or not patients received their prescribed orthoses. Type of orthosis, diabetes as a comorbidity, education, income, sex, and diagnosis were not significant predictors of whether the patient received the orthosis. Qualitative results from the survey revealed that among those receiving their orthoses, 87% experienced improvement in symptoms: 21% felt completely relieved, 66% felt better, 10% felt no different, and 3% felt worse. Conclusion: We found that white patients had almost 3 times the odds of receiving prescribed orthoses as black patients, even after controlling for type of insurance, suggesting race to be the primary driver of discrepancies, raising the question of what can be done to address these inequalities. While large, systematic change will be necessary, some strategies can be employed by those working directly in patient care, such as informing primary care practices of their ability to see patients with limited insurance, limiting blanket refusal policies for government insurance, and educating office staff on how to efficiently work with Medicare and Medicaid. Level of Evidence: Level III, comparative study.